2016
DOI: 10.3389/fneur.2016.00005
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Cells as a Link between Cannabinoids and the Immune Hypothesis of Psychiatric Disorders

Abstract: Psychiatric disorders are one of the leading causes of disability worldwide. Although several therapeutic options are available, the exact mechanisms responsible for the genesis of these disorders remain to be fully elucidated. In the last decade, a body of evidence has supported the involvement of the immune system in the pathophysiology of these conditions. Microglial cells play a significant role in maintaining brain homeostasis and surveillance. Dysregulation of microglial functions has been associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 141 publications
1
32
0
3
Order By: Relevance
“…Indeed, microglial cells are cells of immunity at the cerebral level, and their link with psychiatric manifestations have already been established (Lisboa et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, microglial cells are cells of immunity at the cerebral level, and their link with psychiatric manifestations have already been established (Lisboa et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it is known that the endocannabinoid system may be sensitive to changes in the physiology of the microglial cell (Lisboa et al . ). Indeed, during microglial activation, by a stress or an inflammatory state, the CB2 receptors are more expressed (Walter et al .…”
Section: Introductionmentioning
confidence: 97%
“…It is suggested that some similar brain pathology may be shared by the two psychiatric disorders. In the past decades, a body of literature has supported the implication of immune alterations in MDD and schizophrenia 35. Our previous work indicated that CFH plays a major role in the development of MDD 14.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the endocannabinoid system is an important neuromodulatory system that mediates a broad range of physiological processes [ 1 , 2 ]. Endogenous cannabinoids and its receptors can regulate some biological processes, such as nervous system development, immune homeostasis, and the response to multiple endogenous and environmental insults.…”
Section: Introductionmentioning
confidence: 99%